2017
DOI: 10.1056/nejmoa1615977
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib for Psoriatic Arthritis in Patients with an Inadequate Response to TNF Inhibitors

Abstract: In this trial involving patients with active psoriatic arthritis who had had an inadequate response to TNF inhibitors, tofacitinib was more effective than placebo over 3 months in reducing disease activity. Adverse events were more frequent with tofacitinib than with placebo. (Funded by Pfizer; OPAL Beyond ClinicalTrials.gov number, NCT01882439 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
460
0
36

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 452 publications
(509 citation statements)
references
References 32 publications
13
460
0
36
Order By: Relevance
“…Psoriatic arthritis is an autoimmune disease that affects both joints and the skin. Tofacitinib was found to be superior to placebo in patients with psoriatic arthritis who had previously had an inadequate response to conventional disease modifying agents and TNF inhibitors . Tofacitinib is now approved for this indication (Table ).…”
Section: A Brief Survey Of Approved and Late Phase Jakinibsmentioning
confidence: 99%
“…Psoriatic arthritis is an autoimmune disease that affects both joints and the skin. Tofacitinib was found to be superior to placebo in patients with psoriatic arthritis who had previously had an inadequate response to conventional disease modifying agents and TNF inhibitors . Tofacitinib is now approved for this indication (Table ).…”
Section: A Brief Survey Of Approved and Late Phase Jakinibsmentioning
confidence: 99%
“…In our current process, the consensus was to use three swollen and three tender joints as the threshold disease activity measure. This is in line with several other funding guidelines such as the National Institute for Health and Care Excellence (NICE), the British Society for Rheumatology (BSR) and the British Health Professionals in Rheumatology (BHPR) and the French Society for Rheumatology, as well as most clinical trials of biologic therapy in PsA . Baseline swollen and tender joint count, as well as patient and physician global assessment on a Likert scale of 1‐5, should be documented prior to initiation of biologic therapy to enable subsequent response evaluation.…”
Section: Resultsmentioning
confidence: 59%
“…By contrast, there is growing evidence for bDMARDs, with several RCTs demonstrating improved clinical and radiological outcomes in patients naïve to csDMARD as well as in those with failure of csDMARD or tumor necrosis factor inhibitors (TNFi) . However, the high cost prohibits the widespread use of these drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A report showed that tofacitinib may lead to the inhibition of the functional effects of IL‐23 on memory T‐cells and suppresses the expression of IL‐23 receptor during the stimulation of lymphocytes . Different studies have reported the effect of tofacitinib on enthesitis in PsA . Although this may not be primary or exclusively driven by affecting IL‐23 secretion, yet we believe that JAKi are unique in their mechanism of action by affecting the production of several cytokine and, in this case, also IL‐23.…”
Section: Pathogenic Role Of Il‐23 In Enthesitis From Clinical Datamentioning
confidence: 82%